Case Report and review of the literature: esophageal pleomorphic rhabdomyosarcoma - Pittacolo, Matteo; Vittori, Arianna; Moletta, Lucia; Zanchettin, Gianpietro; Pierobon, Elisa Sefora; Capovilla, Giovanni; Salvador, Renato; Michelotto, Mauro; Valmasoni, Michele (Frontiers in Oncology, 2025)
BackgroundEsophageal rhabdomyosarcoma is an exceedingly rare malignant tumor, with only three cases comprehensively documented in the literature since 1995. Due to its rarity, there is limited information on the epidemiology and diagnosis of this disease, and no standardized treatment protocols have been established. As a result, both the recognition and management of esophageal rhabdomyosarcoma pose significant challenges. The present case report provides valuable insight into the clinical approach to this rare tumor, highlighting the need for further research and investigation to develop more effective diagnostic tools and therapeutic strategies.Case PresentationWe described the case of a 77-year-old male who presented with dyspepsia and anemia, leading to the discovery of an esophageal lesion. At the index endoscopy, histological findings were consistent with esophageal adenocarcinoma. Consequently, the patient was treated with neoadjuvant chemotherapy and Ivor Lewis esophagectomy. Interestingly, on pathological examination the lesion was identified as a pleomorphic rhabdomyosarcoma of the esophagus. Postoperatively, the patient received adjuvant chemotherapy. Subsequently, a subcutaneous metastatic lesion on his right shoulder was treated with a combination of radiotherapy and surgical excision. The patients died twenty-six months after the initial diagnosis.ConclusionsOur case represents one of the few reported instances of esophageal rhabdomyosarcoma, a highly rare and aggressive malignancy, and provides valuable insights into the challenges of diagnosing and managing this disease. Moreover, this is one of the first cases of esophageal rhabdomyosarcoma followed up for more than 24 months. However, given the paucity of data on esophageal rhabdomyosarcoma, there remains a significant unmet need for more comprehensive studies to establish standardized diagnostic and therapeutic protocols.